Gambaran eritrosit urin pada pasien tuberkulosis paru dewasa di RSUP Prof. Dr. R. D. Kandou Manado - Sinaga, Gracia S.; Rambert, Glady I.; Wowor, Mayer F. (e-Biomedik, 2016)
Abstract: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis remains a major global health problem and ranks as the second leading cause of death from an infectious disease worldwide. Anti-tuberculosis drugs, such as streptomycin and rifampicin are nephrotoxic. If the kidney function decreased, especially the glomerulus there can be found blood cells in the urine. A small number of erythrocytes may be found in normal urine, about 0-2 cells per HPF (High Power Field). But more than three erythrocytes per HPF is generally considered hematuria. This study aims to describe about how the urine erythrocytes in adult pulmonary tuberculosis patients at RSUP Prof. Dr. R. D. Kandou Manado. Research design used is descriptive observational research. Samples were urine samples of all pulmonary tuberculosis patients that suit to inclusion criteria. This study was conducted from October to November 2016. The results of chemical urinalysis of urine erythrocytes are negative in 20 patients and positive in 10 patients, while the results of microscopic urinalysis of urine erythrocytes are normal in 26 patients and hematuria in 4 patients. Conclusion: Hematuria mostly found in males, age 56-65 years old, default tuberculosis type, the first category of anti-tuberculosis drugs, the duration of therapy about 3-4 months, and in patients with comorbid disease.Keywords: pulmonary tuberculosis, urinalysis, hematuriaÂ Abstrak: Tuberkulosis merupakan penyakit infeksi yang disebabkan oleh Mycobacterium tuberculosis. Tuberkulosis masih merupakan salah satu masalah kesehatan masyarakat di dunia dan menduduki peringkat kedua penyebab kematian oleh penyakit infeksi di dunia. Obat anti-tuberkulosis seperti streptomisin dan rifampisin memiliki efek nefrotoksik. Apabila fungsi ginjal terutama glomerulus telah rusak maka dapat ditemukan adanya eritrosit dalam urin. Pada urin normal terdapat eritrosit sekitar 0-2 sel/LPB. Jika ditemukan 3 sel/LPB atau lebih, maka disebut hematuria. Penelitian ini bertujuan untuk mengetahui gambaran eritrosit urin pada pasien tuberkulosis paru dewasa di RSUP Prof. Dr. R.D. Kandou Manado. Desain penelitian yang digunakan adalah deskriptif observasional. Sampel penelitian adalah sampel urin sewaktu dari semua pasien tuberkulosis paru yang memenuhi kriteria inklusi. Penelitian dilakukan sejak Oktober-November 2016. Dari hasil pemeriksaan eritrosit urin secara kimia didapatkan hasil negatif pada 20 pasien dan hasil positif pada 10 pasien, sedangkan pemeriksaan mikroskopis eritrosit urin ditemukan hasil normal pada 26 pasien dan hasil hematuria pada 4 pasien. Simpulan: Hematuria didapatkan lebih banyak pada pasien laki-laki, pada kelompok usia 56-65 tahun, pada jenis kasus putus obat, pada jenis pengobatan kategori 1, pada lama pengobatan 3-4 bulan, dan pada pasien dengan penyakit penyerta. Kata kunci: tuberkulosis paru, urinalisis, hematuria